Ethnobotany of Traditional Medicinal Plants as Phytotherapy Agents in Pemenang Timur Village, North Lombok Regency - Putri Indah Sukmawati; Edi Muhamad Jayadi; Firman Ali Rahman (Jurnal Inovasi Pendidikan dan Sains, 2025)
The people of East Juara Village still use plants as additional medicines in treating various types of diseases. The use of plants as medicine is part of local wisdom that needs to be explored and improved again to be preserved before it is lost by the changing times, one of which is through ethnobotanical studies. The purpose of the research is to identify the types of medicinal plants, as well as how they are used and utilized. This study uses a qualitative descriptive approach with the snowball sampling method. Data collection was obtained through interviews, observations, and documentation, with the selection of resource persons based on the snowball sampling method. The results of the study found that there were 68species of plants used as medicine by the people of Pemenang Timur Village, North Lombok Regency, which came from 37 different families. These plants are used to treat 36 types of diseases, either singly or in a mixture. In terms of habitus, the type of plant that is most widely used is the shrub type with a percentage of 31%. Meanwhile, the part of the plant that is most often used is the leaves, with a percentage of 56%. The people of Pemenang Timur Village mostly consume cultivated plants, which reaches a percentage of 59%